Acute kidney injury associated with hypercalcaemic crisis in a patient with primary hyperparathyroidism. (30th July 2018) - Sethi, Jasmine; Kumar, Vivek; Rathi, Manish; Gupta, Krishan Lal
Abstract : Parathyroid or hypercalcaemic crisis is a rare presenting manifestation of primary hyperparathyroidism and usually seen in relation to parathyroid carcinoma and multiple myeloma. We present a middle-aged woman with extreme hypercalcaemia due to parathyroid adenoma presenting as acute kidney injury. This case highlights the need to consider primary hyperparathyroidism in differentials of a patient presenting with severe hypercalcaemia and renal dysfunction. Also this is the second reported case in literature of a patient surviving such extreme hypercalcaemia due to parathyroid adenoma.